Solar power : a true book - Petersen, Christine (New York : Children's Press, 2004)
Describes how the sun's energy suppports all living things on Earth and how it is used as a power resource to create electricity.
Includes bibliographical references and index.
Keywords: Solar energy -- Juvenile literature; Solar energy